The Use of Prepositional Phrases Related to Causal Statements in Folk Tale Translation from Thai into German: A Case Study of the Folk Tale Kraithong: การใช้บุพบทวลีที่แสดงเหตุและผลในงานแปลนิทานพื้นบ้านจากภาษาไทยเป็นภาษาเยอรมัน กรณีศึกษา นิทานไกรทอง - วัชระกวีศิลป วัสมิลล์ (JOURNAL OF LANGUAGE, RELIGION AND CULTURE, 2023)
This article aims to study and analyze the use of prepositional phrases in the translation of the folk tale Krai Thong from Thai to German to demonstrate the use of language in translating from the source text into the target language to make clear and concise and to clearly convey emotions and meanings. However, it does not lose the true content of the original language. In this study, the author specifically collected data and analyzed sentences related the use of prepositional phrases concerning the grammatical topic Kausal in German language instead of using the main clauses and minor clauses. Four prepositions (aus Angst / aufgrund / wegen / vor Zorn) were found and analyzed, leading to the discussion that 1) Prepositional phrases have a linguistic function in terms of translating from the source text into the target language to make the text clear and concise. They can clearly convey emotions and meanings and the text does not lose the true content of the original language. 2) Prepositional phrases can better convey the meanings related to causal statements when compared to adjectives. For instance, it distinguishes the difference between vor Zorn and zornig in relation to their semantic functions. At the initial level of semantic analysis, it can be seen that these two words are synonymous. But when the translator further analyzed the language in the original language, it was found that the original sentence in Thai language is related to the grammatical aspect Kausal in German language. Hence, the prepositional phrase vor Zorn was the proper word to be used in the translated sentence, whereas the word Zornig is related to the grammatical Modal in German language. 3) The prepositional phrase vor Zorn has both semantic function and can be an idiom when analyzing the semantic function. This can further be analyzed that using vor Zorn as an idiom can indicate the language style of the translator in selecting appropriate phrases or idioms for translation to convey the emotions and meanings hidden in the original text.